2020
DOI: 10.21203/rs.3.rs-40089/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health impacts among health workers during COVID-19 in a low resource setting: a cross-sectional survey from Nepal

Abstract: Background: Health care workers exposed to COVID-19 might be at increased risk of developing mental health problems. The study aimed to identify factors associated with anxiety, depression and insomnia among health workers involved in COVID-19 response in Nepal. Methods: This was a cross-sectional web-based survey conducted between April 26 and May 12, 2020. A total of 475 health workers participated in the study. Anxiety and depression were measured using a 14-item Hospital Anxiety and Depression Scale (HADS:… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
130
4
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(169 citation statements)
references
References 40 publications
22
130
4
10
Order By: Relevance
“…Fear of death for HCWs or their relatives double the risk of depression among HCWs. These findings are supported by previous studies [ 21 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Fear of death for HCWs or their relatives double the risk of depression among HCWs. These findings are supported by previous studies [ 21 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…HCWs with past history of psychiatric illness were seven times more likely to have depression than those without such history according to the current study. In line with this finding, other studies [ 23 , 38 ] reported that health workers who had a history of medication for mental health problems had a higher risk to exhibit anxiety, depression, and insomnia symptoms compared with those who had no psychiatric history.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study women had a depressive, anxiety and stress sign more than men according to PHQ9 scale. Gao and et al (31), reported that anxiety turned out serious and frequently problem for female students.in contrary Khanal and et al (33) showed that gender had no signi cant effect on any mental health disorder.…”
Section: Availability Of Data and Materialsmentioning
confidence: 95%
“…5 A timely assessment of mental health status and mental health needs of health workers will help to respond and reduce psychological distress earlier, improve their mental wellbeing and increase the work performance. 6 Healthcare workers like nurses' are the primary group who come in contact with patients, an important source of exposure to infected cases in healthcare settings. Corona Virus Disease 2019 (Covid-19) pandemic has brought all the health care professionals including nurses to work as a frontline member, which may bring threat to mental wellbeing.…”
Section: Introductionmentioning
confidence: 99%